3(x-5)+6=4(2x+3)

Simple and best practice solution for 3(x-5)+6=4(2x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-5)+6=4(2x+3) equation:



3(x-5)+6=4(2x+3)
We move all terms to the left:
3(x-5)+6-(4(2x+3))=0
We multiply parentheses
3x-(4(2x+3))-15+6=0
We calculate terms in parentheses: -(4(2x+3)), so:
4(2x+3)
We multiply parentheses
8x+12
Back to the equation:
-(8x+12)
We add all the numbers together, and all the variables
3x-(8x+12)-9=0
We get rid of parentheses
3x-8x-12-9=0
We add all the numbers together, and all the variables
-5x-21=0
We move all terms containing x to the left, all other terms to the right
-5x=21
x=21/-5
x=-4+1/5

See similar equations:

| 10m-400=600 | | (2x-11)(6x-7)=180 | | x+1/4=-2/3 | | -(1)/(2)(5x-8)-1=6 | | 5+3x4x+2= | | 419.5-2.7x=100 | | 419.5-2.7x=40 | | 5.5-2y=3+2y | | 419.5-2.7x=20 | | 419.5-2.7x=0 | | 8v-49v+8)=8 | | x^2-9x+90=0 | | 16+x=57 | | 6.5(g-7+2g-3(g-5)=0 | | 3x+9=90+9 | | 4-(3^x)=0 | | 35xX=175 | | 12y+8y+y=2y+48+4y | | 2(e-16)=-15 | | 3x-9=90-9 | | 7-3s=s-8+-4s | | 2a+6=15 | | 5^((4+3x))=(1)/(3125) | | 4x-12+54=180 | | -14=-2(s-5) | | 18=2(h+15) | | 1÷4(2x-14)=4 | | 0.18(y-8)+0.04=0.10y-0.3 | | 10=11+3/s | | 71=8q+15 | | -5(v+63)=95 | | 81-x^2=2x |

Equations solver categories